Oxygenated xanthones and biflavanoids from the twigs of Garcinia xanthochymus - Trisuwan K. (Elsevier Ltd, 2014)
Three new xanthones, xanthochymones A-C (1-3), together with six known compounds including two xanthones, three biflavanoids, and one mellein derivative are isolated from the methanol extract of the twigs of Garcinia xanthochymus. Their structures are identified on the basis of their spectroscopic data. Compound 3 displays moderate antibacterial activity against Staphylococcus aureus while compounds 2 and 3 are weakly active against methicillin-resistant S. aureus. © 2014 Elsevier Ltd. All rights reserved.